Sustainable recovery strategies for ecosystem restoration and conservation post-ASGM - Sulaiman; Hatta, Muhammad; Jufri (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Artisanal and small-scale gold mining (ASGM) has significantly contributed to environmental degradation, including deforestation, soil erosion, water pollution, and mercury contamination. This literature review explores sustainable recovery strategies, highlighting successful restoration efforts, challenges, and policy gaps. Method: The study examines existing literature on post-ASGM restoration efforts, focusing on community-led rehabilitation programs, technological innovations, and policy interventions. Data were collected from peer-reviewed journals, policy reports, and case studies to identify key trends, challenges, and best practices in ecosystem recovery. Results: Community involvement plays a crucial role in rehabilitation programs, with local-led reforestation, land reclamation, and sustainable livelihood initiatives demonstrating positive environmental and socioeconomic outcomes. Strengthening community participation through capacity-building, incentives, and participatory governance is essential for long-term success. Technological innovations have significantly contributed to mitigating ASGM-related environmental damage. Mercury-free gold extraction methods, bioremediation, and remote sensing techniques have improved restoration efforts, yet their accessibility remains a challenge in ASGM-affected regions. Increased investment in technology transfer and research collaboration is needed to bridge this gap. Additionally, integrating traditional ecological knowledge (TEK) with modern restoration strategies enhances environmental sustainability while respecting local cultural practices. Despite its potential, TEK is often overlooked in policy frameworks, limiting its broader application. Conclusion: The review identifies policy gaps in existing governance structures, emphasizing the need for stronger enforcement, financial mechanisms, and multi-stakeholder collaboration. Ensuring a balance between conservation goals and local livelihoods requires sustainable economic alternatives such as agroforestry, ecotourism, and responsible mining practices. Collaborative efforts among governments, NGOs, private sectors, and local communities are crucial to fostering long-term ecosystem recovery. Novelty/Originality of this article: This review provides valuable insights for policymakers, environmental organizations, and researchers working towards sustainable ecosystem recovery post-ASGM. It highlights the integration of TEK with scientific approaches, the role of technological innovations in restoration, and the necessity of participatory governance.